STRATEGI ADVOKAT DALAM MENGHADAPI KASUS KONSTITUSI DI MAHKAMAH KONSTITUSI - Daniel Sitohang; Martono Anggusti (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Access to justice is a constitutional right of every citizen, including the right to file cases with the Constitutional Court. However, in practice, several obstacles hinder the fulfillment of this right, particularly for underprivileged communities. One of the main issues is the limited availability of legal assistance in constitutional cases, where many petitioners lack legal representation when submitting their cases to the Constitutional Court. This study employs a normative juridical method with a conceptual approach and literature review. The findings indicate that the role of advocates in constitutional cases is crucial to ensuring the protection of citizens' constitutional rights. However, challenges such as the low involvement of advocates in constitutional cases, limited legal aid funding, and a lack of public legal awareness contribute to the suboptimal access to justice. As a solution, this study proposes the establishment of Constitutional Advocates under the Secretariat General of the Constitutional Court. The presence of Constitutional Advocates is expected to ensure that every citizen, particularly the underprivileged, receives adequate legal assistance in constitutional cases. With supportive regulations and increased legal awareness in society, Indonesia’s constitutional justice system can become more inclusive and equitable